Implementasi Metode WASPAS dalam Sistem Pendukung Keputusan Pemilihan Ketua OSIS di SMK Al-Ikhlas Losari - Najmuddin; Nur Ariesanto Ramdhan; Bambang Irawan (Elkom: Jurnal Elektronika dan Komputer, 2025)
The election of the OSIS chairman at SMK Al-Ikhlas Losari often influences subjectivity, so a goal-oriented system is needed to select the best candidate. This study applies the WASPAS method in a Decision Support System to broadcast OSIS chairman candidates based on criteria such as attendance, integrity, academic achievement, and health. Data were collected through observation, interviews, and literature studies, then processed using Microsoft Excel. The results of the WASPAS calculation yield a Qi preference value, which determines the ranking of candidates transparently. This system reduces subjectivity, increases efficiency, and ensures the selection of competent leaders, supporting the OSIS vision.